How Economic Growth and Rational Decisions Can Make Disaster Losses Grow Faster Than Wealth - Hallegatte, Stephane (2012)
Assuming that capital productivity is higher in areas at risk from natural hazards (such as coastal zones or flood plains), this paper shows that rapid development in these areas -- and the resulting increase in disaster losses -- may be the consequence of a rational and well-informed trade-off between lower disaster losses and higher productivity. With disasters possibly becoming less frequent but increasingly destructive in the future, average disaster losses may grow faster than wealth. Myopic expectations, lack of information, moral hazard, and externalities reinforce the likelihood of this scenario. These results have consequences on how to design risk management and climate change policies.